COVID-19: OPPORTUNITIES IN ISLAMIC FINANCE TO OVERCOME THE CONSEQUENCES OF THE GLOBAL ECONOMIC CRISIS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
It should be acknowledged that the process of the pandemic has demonstrated how critical it is for humanity to approach socio-economic relations in society from an ethical point of view. As everyone knows the fundamental values of Islam put great focus on social justice, equality, and distribution of wealth between the haves and the have nots.  Therefore, in this context, the potential of Islamic microfinance products, including Mudaraba, Salam, Takaful, Zakah, Sadaqat, and Qard-al-hassan, as a response to the global economic crisis during the coronavirus pandemic, was explored.